Čiji je kaj? Narječje između prihvaćanja i odbijanja - Puškar, Krunoslav (Slavia Centralis, 2020)
This paper considers the Croatian Kajkavian dialect from several perspectives. First it is considered from a historical overview: how its polyfunctional literary variant became marginalised at the expense of another literary variant in the era of Croatian nation-building and language standardisation. Among the outcomes of this marginalisation, the author finds a loss of language and regional awareness, language pride and language prestige, and more generally an unfavourable sociolinguistic status of the Kajkavian dialect which continues to the present day. As a result, the second part of this paper deals with a proposal for the present: the introduction of Kajkavian to schools as part of elective courses or extracurricular activities. In this way, the sociolinguistic status of Kajkavian in the educational context would be improved and positive attitudes towards it ensured, which we consider vital due to its present highly negative perception by both speakers and non-speakers.